An Audit of Medicines Reconciliation in Paediatrics. Issue 6 (9th May 2013) - Patel, S; Fletcher, P
Abstract : Medication reconciliation (MR) is obtaining an accurate list of medicines prior to admission and ensuring that the current prescription corresponds to this. It occurs at any point of transfer of patient care. 1, 2 The aim was to collect baseline data on the level of completion of medicines reconciliation for paediatric inpatients by healthcare professionals. Standards 3 : MR should be documented by the admitting healthcare professional in the patient medical record, within 6 h of admission- 100% Paediatric patients will have a medication history taken by a member of the pharmacy team within 72 h, where necessary- 60%. Where it is clear that there is no previous medical history, a repeat medication history by the pharmacy team is not necessary. 100% of known patients or those with a previous medical history will have a drug history documented within 72 h. 100% of discrepancies identified by the pharmacist have been discussed and rectified with the medical team Method: All patients admitted to three medical wards between 5 January 2012 to 19 January 2012 and whose drug chart and notes were available were included in the audit. A pilot was conducted between 5 January 2012 to 6 January 2012. Data were collected after the pharmacist had visited the ward. For each patient, the relevant pages of the drug chart and medical notes were photocopied for quality assurance which was carried out with the project supervisor. Results: 44 patients were included in the audit and 70% (n=31) had a drug history taken on admission (either in A&E or on the ward) 97% (n=30) were completed within 6 h 64% (n=28) had MR performed by a pharmacist 100% (n=28) were completed within 72 h of admission. Nine patients had no past medical history thus not requiring pharmacist MR, three patients may have required a repeat MR and four did require a repeat MR. 11% (n=5) had no MR documented by any healthcare professional. 25% (n=7) patients had an intentional or unintentional discrepancy between pre- and post-admission medication. Ten discrepancies were identified with four intentional changes and six were unintentional which were rectified on discussion between the doctor and ward pharmacist. Conclusions: Baseline data has been obtained regarding medicines reconciliation in paediatrics. The results have highlighted that doctors are not always documenting MR and pharmacists are not carrying out repeat MR in patients who require one, for example, those with a past medical history, however all discrepancies identified are clarified and when necessary are rectified.